Meadow. “Patchwork of Practice” as autoethnography for personal and professional development - Meakin, Beverley Joan (Murmurations: Journal of Transformative Systemic Practice, 2021)
In this paper, I demonstrate the use of an exercise that I devised as a teaching intervention for student counsellors and therapists – Patchworks of Practice (Meakin, 2019). It facilitates exploration of contextual influences on their human being and aids reflexivity on how these influences shape their practice. I explain how Patchworks of Practice work and show how I adapted the exercise as a form of autoethnography. I share learning of the process and findings from one part of my doctoral research in which I used autoethnography to explore how my personal influences shaped me and my way of working as a couple therapist and as a university lecturer teaching on counselling courses. I use examples of my own patches and my reflections on them to illustrate the reflective research process and discuss my learning. The Patchworks of Practice exercise has been useful in collating different theoretical concepts for me as a couple therapist and my approach to teaching. It offers a way of highlighting resources for navigating professional landscapes particularly in times of uncertainty such as during the pandemic. In this practitioner research, I extend the patchwork metaphor to a rural landscape to communicate how I see my life and the contexts in which it has evolved - and which have shaped it. I hope this paper will inspire others to use the Patchwork of Practice exercise in their own reflexive learning, self-supervision and research.